Community Service at Nogotirto Elementary School: From Yogyakarta's Corner, Looking at the World - An Exciting Adventure to Explore the World - Iswardhana, Muhammad Ridha; Maharani, Gita Ardya; Nurjannah, Lukluulhayu; Wulandari, Rizky (Jurnal Pengabdian West Science, 2025)
This community service program addresses the limited access to adequate education for children in the outskirts of Yogyakarta. The community service program "From Yogyakarta's Corner, Looking at the World - Exciting Adventures Exploring the World" was held at Nogotirto Public Elementary School. The purpose of the community service activity was to enrich students' learning experiences, foster awareness of their social contributions, and create a fun and inspiring learning environment. Interactive methods were implemented through educational games, storytelling, and motivational mentoring. The International Relations material was simplified to an introduction to world regions and their relationship to Indonesia. Children demonstrated active engagement through questions about the ethics of friendship, role models, and a sense of security. The main obstacles were operational: variations in student abilities, managing class rhythms, and limited teaching resources. Overall, this activity demonstrated that structured and adaptive interventions can strengthen students' cognitive-emotional support while strengthening their social solidarity. School-campus collaboration ensures that the program is contextual, not ceremonial, and provides a basis for improving teaching materials and sustaining more regular mentoring.
Keywords: Community Service; Nogotirto State Elementary School; Yogyakarta Faces the World; Exciting Adventures Exploring the World